Xanomeline treatment attenuates cocaine self-administration in rats and nonhuman primates - Marsh, Samuel A.; Heslep, Nicholas; Paronis, Carol A.; Bergman, Jack; Negus, S. Stevens; Banks, Matthew L. (Neuropharmacology, 2025)
The lack of an FDA-approved pharmacotherapy to combat cocaine use disorder (CUD) is an ongoing and urgent public health challenge. Emerging evidence suggests that the muscarinic acetylcholine system modulates mesolimbic dopamine release and thus may serve as a suitable target for novel CUD medications. The M1/M4-preferring muscarinic agonist xanomeline was recently approved by the Food and Drug Administration for schizophrenia management, and a previous study in male rats suggested that xanomeline treatment attenuated cocaine self-administration in a cocaine-vs-food choice procedure. The present study was conducted to further examine xanomeline treatment effectiveness on cocaine self-administration in male and female rats and nonhuman primates. Both male and female rats and monkeys were trained to self-administer cocaine during daily behavioral sessions. Repeated xanomeline treatment significantly decreased cocaine choice in rats similar to both pharmacological (amphetamine maintenance) and non-pharmacological (increasing alternative reinforcer value) positive controls. In separate groups of monkeys, acute xanomeline pretreatment decreased cocaine-vs-food choice in three out of four monkeys and selectively decreased cocaine-, but not food-maintained responding, under a multiple schedule of cocaine and food reinforcement in three out of four monkeys. Overall, the consistent effectiveness of xanomeline to reduce IV cocaine self-administration in both rodents and nonhuman primate supports its further evaluation as a CUD medication in humans. [Display omitted] •Xanomeline treatment attenuated cocaine choice in male and female rats.•Acute xanomeline treatment decreased cocaine SA in 7 out of 8 monkeys.•Xanomeline effects were similar to amphetamine maintenance in rats.